2020
DOI: 10.1002/asia.201901680
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Cascade Biotransformation for Efficient Synthesis of Benzyl Alcohol and Its Analogs

Abstract: Benzyl alcohol is a naturally occurring aromatic alcohol and has been widely used in the cosmetics and flavor/fragrance industries. The whole‐cell biotransformation for synthesis of benzyl alcohol directly from bio‐based L‐phenylalanine (L‐Phe) was herein explored using an artificial enzyme cascade in Escherichia coli. Benzaldehyde was first produced from L‐Phe via four heterologous enzymatic steps that comprises L‐amino acid deaminase (LAAD), hydroxymandelate synthase (HmaS), (S)‐mandelate dehydrogenase (SMDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
22
1
Order By: Relevance
“…When the recombinant E. coli was fed with 5 mM of m ‐f‐DL‐phenylalanine as substrate, 2.54 mM m ‐fluorobenzylamine was obtained (Figure 2b), whereas m ‐fluoro‐D‐phenylalanine remained nearly unreacted during the biotransformation process (Figure S3). LAAD from P. mirabilis predominantly catalyzes the deamination of L‐amino acids [22] and it has been used for resolving the racemic mixture of D and L‐amino acids [21] . Current observations also suggested that LAAD is a good candidate for resolving the racemic mixture of nonnatural amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the recombinant E. coli was fed with 5 mM of m ‐f‐DL‐phenylalanine as substrate, 2.54 mM m ‐fluorobenzylamine was obtained (Figure 2b), whereas m ‐fluoro‐D‐phenylalanine remained nearly unreacted during the biotransformation process (Figure S3). LAAD from P. mirabilis predominantly catalyzes the deamination of L‐amino acids [22] and it has been used for resolving the racemic mixture of D and L‐amino acids [21] . Current observations also suggested that LAAD is a good candidate for resolving the racemic mixture of nonnatural amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…As shown from Figure 2a and Figure S2 Figure S3). LAAD from P. mirabilis predominantly catalyzes the deamination of L-amino acids [22] and it has been used for resolving the racemic mixture of D and L-amino acids. [21] Current observations also suggested that LAAD is a good candidate for resolving the racemic mixture of nonnatural amino acids.…”
Section: Synthesis Of Benzylamine Analogues Via One-pot Whole-cell Bimentioning
confidence: 99%
“…Recently, PmLAAD has been expressed together with two additional enzymes in an artificial enzyme cascade in E. coli with the aim to produce benzyl alcohol analogs. This approach demonstrated the ability of PmLAAD to produce optically pure D-m-fluoro-phenylalanine from the corresponding racemic mixture [58]. In addition, a 4-point variant of this enzyme has been exploited to produce D-phenylalanine, exhibiting a conversion of 49.5% after 7 h [59].…”
Section: Production Of D-amino Acids By Enantioselective Deamination/deracemization Using L-amino Acid Deaminasementioning
confidence: 99%
“…Moreover, ortho and meta fluorinated mandelic acids were also synthesized in the same method (Yields = 37 ± 0.4% and 47 ± 1.8%). Also starting from substrate fluoro- l -phenylalanine, fluoro-benzyl alcohol was successfully synthesized in a multi-enzymatic system of five enzymes, including LAAD, HMS, l -mandelate dehydrogenase (LMDH), benzoylformate decarboxylase (BFD), and phenylacetaldehyde reductase (PAR) (Yield = 633.17 mg/L) (Figure S11 ) (Liu et al 2020 ).…”
Section: Enzymatic Synthesis Of Fluorinated Compoundsmentioning
confidence: 99%